Formulasi Dan Uji Aktivitas Sediaan Sabun Mandi Cair Ekstrak Etanol Daun Kapuk (Ceiba pentandra (L.) Gaertn) Terhadap Pertumbuhan Bakteri Staphylococcus Aureus - A. Suparlan Isya Syamsu; Muhammad Yusuf; Arfiani; Dedy Maruf (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Kapok leaf (Ceiba pentandra (L.) Geartn) is a plant that contains several secondary metabolites in the form of alkaloids, flavonoids, tannins and saponins which have antibacterial properties. One of the pharmaceutical dosage forms that can be used to maintain healthy skin is antibacterial liquid bath soap. This study aims to determine whether kapok leaf extract (Ceiba pentandra (L.) Geartn) can be formulasited into a liquid bath soap that is physically-chemically stable and has antibacterial activity against Staphylococcus aureus bacteria. This type of research is an experimental study with a pretest and posttest only control design for testing the physical and chemical stability of the liquid bath soap formulasition and a posttest only control group design for testing the antibacterial activity of Staphylococcus aureus. In this study, there were 5 treatment groups, namely, F0 as a base without kapok leaf extract, F1 as a positive control of liquid lifebuoy soap, F2 as a preparation using 8% kapok leaf extract, F3 as a preparation of 9% kapok leaf extract and F4 using kapok leaf extract preparation 10%. The results of the research on liquid bath soap preparations from leaf extract of Kapok leaf (Ceiba pentandra (L.) Geartn) can be formulasited into liquid bath soap that has good stability from organoleptic tests, pH, viscosity, homogeneity, foam stability and free alkali with concentration antibacterial activity tests. 8% inhibition zone 15.8 mm, 9% inhibition zone 16.5 mm and 10% inhibition zone 18.1 mm. The formulasi for liquid bath soap with kapok leaf extract (Ceiba pentandra (L.) Geartn) can be formulasited with concentrations of 8%, 9% and 10% which are physically and chemically stable with strong antibacterial activity.